PELATIHAN PENGEMBANGAN DESAIN MOTIF BATIK BAGI PENGRAJIN UKM “CAHAYA SARI” - Veronika Kristanti P.L. (Abdi Seni, 2020)
Batik is a world heritage that has been avowed by UNESCO and has become a traditional culture in  Indonesia.  Knowledge  about  batik  becomes  a  must  for  people  in  Surakarta.  Batik  has  been developed in all aspects of society, covering spreading information about batik, the process of batik making, marketing, and area location (industry centre). The training activity concerning the draft of batik motive design, formal as well as non formal in the education institutions, governmental institutions, and private institutions have increased. Public society is hoped to take part in supporting the program. The training aims to introduce batik as well as give an extra skill concerning to plan the batik motive design. This activity uses the methods of speech, demonstration, and autonomous assignment. The problem of training includes how to describe material in developing batik motive design to the craftmen of batik tulis Cahaya Sari, Plupuh and how the process of batik tulis making in Cahaya Sari, Plupuh. Result of the training is that the employee and society around Cahaya Sari are able to plan batik motive design by developing batik motive belong to the institution.Keywords: design, motive, batik, Cahaya Sari.